Magnetic N-doped and undoped carbon nanotubes as catalysts for wet peroxide oxidation - Martin-Martinez, Maria (2015)
Magnetic Fe-containing N-doped and undoped carbon nanotubes (N-CNT and CNT, respectively) have been prepared and tested in the catalytic wet peroxide oxidation (CWPO) of 4-nitrophenol (4-NP; 5 g L-1) at relatively mild operating conditions (atmospheric pressure, T = 50 ºC, pH = 3, catalyst/adsorbent load = 2.5 g L-1 and [H2O2]0 = 17.8 g L-1).